DETERMINAN STRUKTUR MODAL PADA PERUSAHAAN INDUSTRI KOMPONEN OTOMOTIF DI BURSA EFEK INDONESIA - Putra, I Gede Pawarista Susila; Candraningrat, Ica Rika (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.03.TAHUN.2023DO - 10.24843/EEB.2023.v12.i03.p13, 2023)
Capital structure is a comparison between debt and company capital. Capital structure is important to consider to avoid financial difficulties. The aim of this study is to determine the effect of profitability, asset structure, firm size, and growth rate on capital structure. This research was conducted at automotive component industry companies that are listed on the Indonesia Stock Exchange for the 2016-2020 period. The data used is quantitative data with secondary data sources published by the Indonesia Stock Exchange. The samples used in the study were 10 companies through purposive sampling methods. This study used non-participant observation methods. The analysis technique used is multiple linear regression. Based on the results of the analysis found that profitability, company size, and growth rate had no effect on capital structure, and asset structure had a positively affects on capital structure. Management is expected to be able to make the right decisions in order to achieve an optimal capital structure .